2019
DOI: 10.3390/nu11092013
|View full text |Cite
|
Sign up to set email alerts
|

A Diet High in Processed Foods, Total Carbohydrates and Added Sugars, and Low in Vegetables and Protein Is Characteristic of Youth with Avoidant/Restrictive Food Intake Disorder

Abstract: Avoidant/restrictive food intake disorder (ARFID) is characterized in part by limited dietary variety, but dietary characteristics of this disorder have not yet been systematically studied. Our objective was to examine dietary intake defined by diet variety, macronutrient intake, and micronutrient intake in children and adolescents with full or subthreshold ARFID in comparison to healthy controls. We collected and analyzed four-day food record data for 52 participants with full or subthreshold ARFID, and 52 he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
48
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 61 publications
7
48
1
1
Order By: Relevance
“…Despite similar low weight and leptin levels in ARFID and AN, a greater waist‐to‐hip ratio (marker of visceral fat) was observed in ARFID. This may reflect dietary differences, that is, a calorie‐dense diet in ARFID (Harshman et al, ) versus a low‐calorie diet in AN. However, waist‐to‐hip ratio no longer differed after controlling for age, indicating that this may simply reflect differences in developmental stage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite similar low weight and leptin levels in ARFID and AN, a greater waist‐to‐hip ratio (marker of visceral fat) was observed in ARFID. This may reflect dietary differences, that is, a calorie‐dense diet in ARFID (Harshman et al, ) versus a low‐calorie diet in AN. However, waist‐to‐hip ratio no longer differed after controlling for age, indicating that this may simply reflect differences in developmental stage.…”
Section: Discussionmentioning
confidence: 99%
“…However, ARFID is driven by low appetite, sensory sensitivities, and/or fear of aversive consequences, rather than body image concerns. While individuals with AN often limit food intake to low‐calorie options, those with ARFID favor a calorie‐dense diet high in processed foods, carbohydrates, and added sugars, and low in vegetables and protein (Harshman et al, ). Unlike AN (characterized by low weight), ARFID spans the weight spectrum from underweight to obesity, demonstrating the heterogeneity and complexity of its underlying pathophysiology.…”
Section: Introductionmentioning
confidence: 99%
“…According to the current evidence, we support the need for diet diversification as part of therapeutic interventions for ARFID to reduce the risk of nutrient insufficiencies and related complications [96].…”
Section: Arfid (Avoidant/restrictive Food Intake Disorder)mentioning
confidence: 89%
“…Electrolyte imbalances, fat-soluble and B vitamins deficiency as well as mercury toxicity may be associated problems [93][94][95]. Harshman et al demonstrated that children with full or sub-threshold ARFID have a significantly higher intake of added sugars, and a lower intake of vitamins K and B12, consistent with limited vegetable and protein intake compared to healthy controls [96].…”
Section: Arfid (Avoidant/restrictive Food Intake Disorder)mentioning
confidence: 99%
“…Clinical descriptions of avoidant/restrictive food intake disorder highlight a reduced dietary intake of a limited volume and variety of foods. For a systematic characterization of intake, Harshman et al [9] evaluated the dietary variety in youth aged 9-22 years with this disorder using food records. Individuals with full or subthreshold avoidant/restrictive food intake disorder reported a lower consumption of vegetables or fruit, lower intake of protein, and relatedly, of specific vitamins (e.g., vitamins K and B12), but a higher intake of added sugars and total carbohydrates when compared to healthy controls.…”
Section: Clinical Presentation Of Avoidant/restrictive Food Intake DImentioning
confidence: 99%